Implementation of Secure Bank Authentication using Visual Cryptography and Image Processing - Mehta, B; Varshney, T; Mandloi, Y; Belel, J; Deshmukh, V (International Journal of Computer Sciences and Engineering, 2025)
With the advent of e-commerce and electronic transactions the need for development of secured systems has grown tremendously. The need for security of information is especially affecting the banking sector. This paper implements an algorithm which proposes an efficient way for decreasing forgery during bank transactions using Visual Cryptography and Image Processing. Visual Cryptography is a generic cryptography technique which takes an image as input for encryption and makes use of human visual system rather than automated computing machines for decryption. Here we use a modified version of Visual Cryptography in which a combination of mechanical process and computation process is used for decryption. Due to the ease of implementation, this technique can be implemented by the people with non-technical background. It encrypts the visual data by dividing it into shares and decrypts the data by stacking some or all shares. Image Processing is used to perform operations on the image. The technique used in this paper works on the signature of the account holder for authentication.